Proceso de atención nutricional en paciente masculino de 50 años de edad con hipertensión arterial. - Morales Carriel, Kevin Steven (2022)
The present clinical case is based on a 50-year-old male patient from the city of Vinces with a medical diagnosis of arterial hypertension. Blood pressure is the force that blood exerts against the walls of the arteries. According to the values of the blood pressure reading can be classified as follows: Normal pressure, Prehypertension, Grade I hypertension, Grade II hypertension; Its diagnosis is the result between the medical history and the auscultation technique of the first and fifth phases of Korotkoff sounds. The general objective of this clinical case is to make an eating plan to improve the nutritional and physiological status of the patient and avoid cardiovascular risks, we proceed to obtain the informed consent of the nutritional treatment, then the nutritional status is evaluated, a food plan is given, in addition to providing the corresponding nutritional education and finally it is concluded by determining the nutritional status of the patient, its comprehensive nutritional diagnosis is obtained through anthropometric, biochemical, clinical and dietary indicators.